(x-1)(-3-2i)(-3+2i)=0

Simple and best practice solution for (x-1)(-3-2i)(-3+2i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-1)(-3-2i)(-3+2i)=0 equation:


Simplifying
(x + -1)(-3 + -2i)(-3 + 2i) = 0

Reorder the terms:
(-1 + x)(-3 + -2i)(-3 + 2i) = 0

Multiply (-1 + x) * (-3 + -2i)
(-1(-3 + -2i) + x(-3 + -2i))(-3 + 2i) = 0
((-3 * -1 + -2i * -1) + x(-3 + -2i))(-3 + 2i) = 0
((3 + 2i) + x(-3 + -2i))(-3 + 2i) = 0
(3 + 2i + (-3 * x + -2i * x))(-3 + 2i) = 0

Reorder the terms:
(3 + 2i + (-2ix + -3x))(-3 + 2i) = 0
(3 + 2i + (-2ix + -3x))(-3 + 2i) = 0
(3 + 2i + -2ix + -3x)(-3 + 2i) = 0

Multiply (3 + 2i + -2ix + -3x) * (-3 + 2i)
(3(-3 + 2i) + 2i * (-3 + 2i) + -2ix * (-3 + 2i) + -3x * (-3 + 2i)) = 0
((-3 * 3 + 2i * 3) + 2i * (-3 + 2i) + -2ix * (-3 + 2i) + -3x * (-3 + 2i)) = 0
((-9 + 6i) + 2i * (-3 + 2i) + -2ix * (-3 + 2i) + -3x * (-3 + 2i)) = 0
(-9 + 6i + (-3 * 2i + 2i * 2i) + -2ix * (-3 + 2i) + -3x * (-3 + 2i)) = 0
(-9 + 6i + (-6i + 4i2) + -2ix * (-3 + 2i) + -3x * (-3 + 2i)) = 0
(-9 + 6i + -6i + 4i2 + (-3 * -2ix + 2i * -2ix) + -3x * (-3 + 2i)) = 0
(-9 + 6i + -6i + 4i2 + (6ix + -4i2x) + -3x * (-3 + 2i)) = 0
(-9 + 6i + -6i + 4i2 + 6ix + -4i2x + (-3 * -3x + 2i * -3x)) = 0

Reorder the terms:
(-9 + 6i + -6i + 4i2 + 6ix + -4i2x + (-6ix + 9x)) = 0
(-9 + 6i + -6i + 4i2 + 6ix + -4i2x + (-6ix + 9x)) = 0

Reorder the terms:
(-9 + 6i + -6i + 6ix + -6ix + 4i2 + -4i2x + 9x) = 0

Combine like terms: 6i + -6i = 0
(-9 + 0 + 6ix + -6ix + 4i2 + -4i2x + 9x) = 0
(-9 + 6ix + -6ix + 4i2 + -4i2x + 9x) = 0

Combine like terms: 6ix + -6ix = 0
(-9 + 0 + 4i2 + -4i2x + 9x) = 0
(-9 + 4i2 + -4i2x + 9x) = 0

Solving
-9 + 4i2 + -4i2x + 9x = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 4i2 + -4i2x + 9 + 9x = 0 + 9

Reorder the terms:
-9 + 9 + 4i2 + -4i2x + 9x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 4i2 + -4i2x + 9x = 0 + 9
4i2 + -4i2x + 9x = 0 + 9

Combine like terms: 0 + 9 = 9
4i2 + -4i2x + 9x = 9

Add '-9x' to each side of the equation.
4i2 + -4i2x + 9x + -9x = 9 + -9x

Combine like terms: 9x + -9x = 0
4i2 + -4i2x + 0 = 9 + -9x
4i2 + -4i2x = 9 + -9x

Reorder the terms:
-9 + 4i2 + -4i2x + 9x = 9 + -9x + -9 + 9x

Reorder the terms:
-9 + 4i2 + -4i2x + 9x = 9 + -9 + -9x + 9x

Combine like terms: 9 + -9 = 0
-9 + 4i2 + -4i2x + 9x = 0 + -9x + 9x
-9 + 4i2 + -4i2x + 9x = -9x + 9x

Combine like terms: -9x + 9x = 0
-9 + 4i2 + -4i2x + 9x = 0

The solution to this equation could not be determined.

See similar equations:

| -6x+11x-59=41 | | b-5=14 | | (8x-7)(3t+9)=0 | | 2(s+3)+4s-5=148+s | | 7h+9j-3h-j= | | 5x-4y=39 | | 4x+6-11x=8 | | 144x-54=18(8x-3) | | 4x-6x+21=5x+35 | | 4x-10+9+6x=34 | | x+1=3+x | | -8d+1=-3 | | 4(x-6)=-3x-17 | | 4x+8-7x+2=5x-8x+7 | | 24x-4+3=24x+12-10 | | 5-3n=10 | | 3x=12x^2 | | 80-k=41 | | 3x-4y=16*x | | 2x^2+4x-4=-6 | | 6(4b-2c)+9f= | | 5y^2-40y^2=0 | | 10(t-4)+4t=7(2t-5)-9 | | 6x+4=6x-9 | | 3x-6+4x-3=180 | | 6+7n=41 | | 2(2r+3)=10r | | 3ax-4x= | | 45+.02x=50+.3x | | 25x^2+y^2-100x-125=0 | | -9x^2-2x+4=8 | | 2X-3=20x |

Equations solver categories